"It Makes Me Feel Many Different Things": A Child's Relationships to Israel over Time. Issue 2 (3rd April 2021) - Zakai, Sivan
ABSTRACT: This article offers a detailed study of one child's relationships to Israel from kindergarten (2012–2013 academic year) through 7th grade (2019–2020 academic year). By tracing Avigail over the course of eight years, I argue that children do not develop "a relationship" with Israel but rather many different relationships over time. Using a combination of qualitative methods including semi-structured interviews, image and music elicitation, storytelling exercises, and parental communications, this case study uses one child's many different conceptions of and relationships to Israel over the course of her childhood and adolescence to shed light on key questions in Israel education.